Occupational Stress Perceived By Hill Farmwomen of Jaunsar in Manual Chaff Cutting - Joshi, Kushagra; Pandey, B M; Khulbe, R K; Pattanayak, Arunava (Indian Journal of Hill Farming, 2018)
Manual chaff cutting is an activity which is carried out mainly by women. It is a tedious and time consuming activity. The force exerted while cutting the chaff with a sharp tool without any safety measure and the static position adopted may pose work related musculoskeletal disorders among farmwomen performing the activity. The present study was intended to evaluate the occupational stress posed by chaff cutting activity to farmwomen in terms of postural risk factors involved. Subjects were observed in their normal work conditions. Their postures, number of repetitive movements of the dominant hand were observed and recorded. Rapid upper lumbar analysis technique was used to analyse postural stress. Subjective responses on exertion were also recorded. This study found that there are ergonomic risk factors in manual chaff cutting, which may lead to the development of work related musculoskeletal disorders and in turn may affect productivity and quality of work. Women most often maintain static positions for certain limbs or are involved in repetitive activities while performing the activity. Need for technological and ergonomic interventions are emphasized.